Kedungwinong Karst Mapping: Determining Tourism Locations and Their Preservation - Eva Banowati; Heri Tjahjono; M Fikri Amrullah; Ahmad Dzulfiqar; Doni Doni; Fauzi Firmanzah; Satya Budi Nugraha; Siti Nurindah Sari (Universitas Pendidikan Ganesha, 2024)
Improving the quality of Karst Kedungwinong sub-Karst Kendeng Mountains is necessary, as a nature scene that can be optimized into a tourist village that delivers unique and attractive attractions. This research discovers the spread of potential tourism associated with Karst conditions and co-conservation. As data providers for Karst and Kedungwinong Caves, these maps are needed to compile tourism, sports, and conservation packages. Tourist location survey research implements an integrated three-pillar blue economy development paradigm to drive economic growth in managing sustainable karst resources. The results of research conducted in Kedungwinong Village, Sukolilo Prefecture, Pati District, found 3 points of location of cliff climbing and nine caves that are potentially tourist locations. The location can be optimized by the residents to be further managed so that it becomes a tourist destination and positively impacts the community's economy.